1239 AGEING WELL IN FRAILTY: DEVELOPING A PRACTICAL MODEL FOR USE IN COMMUNITY PRACTICE TO IMPROVE PATIENT REPORTED WELLNESS. (16th January 2023) - Thomas, D
Abstract: Introduction: Empowering patients to 'age well' (NHS England Long Term Plan, 2019) has become a key driver to meet the rising demand for healthcare. Despite a growing body of evidence regarding ageing well and the benefits of patient empowerment (Selman et al, 2017) and reducing demand on resources (Age UK, 2020), there remains confusion regarding applied meaning for the spectrum of older persons health. This research will consider expert view on the topic of 'ageing well' related to the predictable patterns of ageing. The aims of this study will be to develop a new interventional frailty stratification model to best meet the needs in advancing frailty. Method: This research study will incorporate a systematic literature review alongside patient and carer focus groups to inform initial questionnaire design for a modified Delphi panel of mixed professional experts. The overall aim of undertaking rounds of questionnaire and subsequent survey will be to arrive at consensus expert view to fulfil the research aims of identifying a conceptual approach to be further tested in community clinical practice. Results: The results of the study will inform a defined model of intervention to guide community practitioners in preventative care for frailty. Testing of the intervention will consider impact upon individuals, clinicians, and ongoing frailty trajectory. Conclusion: At the time of the Autumn conference, the research study will be at recruitment stage for the modified Delphi panel. This abstract application is requesting support to share the background and progress to date with conference delegates to actively support a modified Delphi research process. The opportunity to showcase the study and network with participants to gauge interest in the ageing well research area would be a valued way to recruit an expert panel with the aim of improving care in this emerging and exciting aspect of older person's care.